Economy-wide effects of input subsidies in Malawi: Market imperfections and household heterogeneity - Sofie Waage Skjeflo; Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
The potential bene ts of providing subsidized inputs to farm-households in developing coun- tries may reach well beyond the targeted households. More speci cally, increased food production and demand for rural labor may bene t poor households through lower food prices and higher rural wages. However, two recent studies of a large input subsidy program in Malawi nd that these e ects are smaller than expected based on anecdotal evidence and previous studies using simulation models. In this paper we provide a potential explanation for this nding by using six farm-household programming models to show how market imperfections limit households' ability to take advantage of cheaper inputs. Our ndings suggest that input subsidy programs could be combined with improved market infrastructure and market access in order to increase non-bene ciary households' bene ts from input subsidies.
Keywords: Q12; Q18; 330; Input subsidies; Malawi; Farm-household models